Using Social Media for English Language Learning by EFL University Students: A Mixed-Methods Study - Tubagus Zam Zam Al Arif; Urip Sulistiyo; Reli Handayani (Celt: A Journal of Culture, English Language Teaching & Literature, 2020)
The purpose of this study is to investigate the usage of social media for English language learning by students at a state university in Jambi, Indonesia. a mixed-method approach was applied in this study. To collect data for this study, a survey and a semi-structured interview were used. The questionnaire was completed by 137 students, and 10 were interviewed randomly from those who completed the questionnaire. The quantitative data from the questionnaire were analyzed using basic statistical analysis, while the data from the interviews were analyzed using phenomenological case analysis combined with coding thematically. This study investigates students’ perceptions towards the use of six popular social media (Facebook, WhatsApp, Snapchat, Instagram, Telegram, and Twitter) in learning English as a foreign language. The results of this study revealed that students utilize a variety of social media platforms, particularly Instagram and Facebook. They showed positive attitudes towards the use of social media for learning English. The students perceived that social media plays an important role to improve their English language skills. In addition, the social media which are mostly used for learning English by EFL university students is Instagram, and they use the social media for learning English as additional (optional) language learning tools in their spare time